2021
DOI: 10.3390/antiox10091383
|View full text |Cite
|
Sign up to set email alerts
|

Tocotrienols as an Anti-Breast Cancer Agent

Abstract: In the past few years, breast cancer has become the most prevalent type of cancer. The majority of patients receive combinatorial chemotherapy treatments, which may result in increased risk of developing drug resistance, a reduced quality of life, and substantial side effects. Treatment modalities that could lessen the physical toll of standard treatments or act in synergy with chemotherapeutic treatments would benefit women worldwide. Research into tocotrienols has thus far demonstrated their potential to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 69 publications
0
14
0
Order By: Relevance
“…199 Among the different types of oxidative damage, DNA oxidation, protein oxidation, and lipid peroxidation are known to produce carcinogenesis, and tocotrienols were identified as having anti-cancer properties that ameliorated the malignant tumors by apoptosis, cell cycle arrest, and disrupted DNA replication and curbed metastasis. 199 DNA oxidation impairs the DNA replication process, and transcription, and upregulates transversion mutations, protein oxidation will lead to peptide chain breakages and susceptibility to proteolysis, while lipid peroxidation results in cell membrane damage in all membrane-bound organelles. 200 Disruption of the plasma membrane would result in the inactivation of signal transduction by denaturing receptors and enzymes.…”
Section: Link Between Antioxidant and Antiinflammatory Properties Of ...mentioning
confidence: 99%
See 1 more Smart Citation
“…199 Among the different types of oxidative damage, DNA oxidation, protein oxidation, and lipid peroxidation are known to produce carcinogenesis, and tocotrienols were identified as having anti-cancer properties that ameliorated the malignant tumors by apoptosis, cell cycle arrest, and disrupted DNA replication and curbed metastasis. 199 DNA oxidation impairs the DNA replication process, and transcription, and upregulates transversion mutations, protein oxidation will lead to peptide chain breakages and susceptibility to proteolysis, while lipid peroxidation results in cell membrane damage in all membrane-bound organelles. 200 Disruption of the plasma membrane would result in the inactivation of signal transduction by denaturing receptors and enzymes.…”
Section: Link Between Antioxidant and Antiinflammatory Properties Of ...mentioning
confidence: 99%
“…Thus, the therapeutic value of vitamin E compounds, particularly the tocotrienols is further enhanced due to its ability to stimulate dual roles by which its anti‐cancer properties are augmented 198 . The prolonged localized cellular inflammatory reactions (generated by dysfunctional electron transport chain in mitochondria, ER and cell membrane, nicotinamide adenine dinucleotide phosphate [NADPH] oxidase, peroxidases, and nitric oxide synthase) can give way to tumorigenesis from which cancers arise, and those cancers have been attenuated by tocotrienols 199 . Among the different types of oxidative damage, DNA oxidation, protein oxidation, and lipid peroxidation are known to produce carcinogenesis, and tocotrienols were identified as having anti‐cancer properties that ameliorated the malignant tumors by apoptosis, cell cycle arrest, and disrupted DNA replication and curbed metastasis 199 .…”
Section: Antioxidant and Anti‐inflammatory Activities Of Tocotrienolmentioning
confidence: 99%
“…Vitamin E is a mixture of eight lipophilic isomers4 saturated tocopherols and 4 unsaturated tocotrienols. , Tocopherols, the major constituent of vitamin E, have been extensively studied on its possible cancer prevention activities (reviewed in ref ). Results from earlier tocopherol studies on cancer prevention were disappointing.…”
Section: Bioactive Compounds In Cancer Chemopreventionmentioning
confidence: 99%
“…Another group of natural Vitamin E in particular, tocotrienols, has at least the same anti-oxidant capacity as tocopherols, but is less readily stable . Interestingly, research on tocotrienols has demonstrated their potential as anti-breast cancer agents. ,, Of the tocotrienols, α-tocotrienol has the highest bioavailability, while the γ-tocotrienol and δ-tocotrienol isoforms have more profound anti-cancer properties . For example, the effective anti-tumor activity of γ-tocotrienol induced apoptosis in breast cancer cell lines via upregulation of extrinsic death receptor signaling DR5 .…”
Section: Bioactive Compounds In Cancer Chemopreventionmentioning
confidence: 99%
See 1 more Smart Citation